Pengaruh Brand Image, Promosi Dan Quality Of Service Terhadap Loyalitas Pelanggan Rocket Chicken Ngadiluwih - Dewi, Septi Novita; Sholihin, Ustadus; Najibul Zamzam, Nurali Agus (Jurnal Cendekia Manajemen (JCM); Vol 3 No 2 (2025): JulyDO - 10.32503/jcm.v3i2.7125, 2025)
This study aims to analyze the influence of brand image, promotion, and quality of service on customer loyalty at Rocket Chicken Ngadiluwih Kediri. The research is motivated by increasing competition in the fast food industry and the need for companies to retain customers through strong brand positioning, attractive promotions, and excellent service. A quantitative approach was used with a descriptive design, involving 110 respondents selected using the Hair et al. sampling formula. Data were collected using a structured questionnaire and analyzed through SPSS version 25 using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The findings show that brand image, promotion, and service quality significantly influence customer loyalty both partially and simultaneously. Theoretically, the study strengthens the concept of customer loyalty formation through integrated marketing variables. Practically, the results suggest that Rocket Chicken should enhance its service quality and promotional strategies while maintaining a strong brand image to improve customer retention and satisfaction. These findings offer insights